2018
DOI: 10.1371/journal.pone.0199516
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of survivourship and function (grazing and behaviour) of three gastropod species used as clean-up crew for the marine aquarium trade

Abstract: Several million gastropods are collected each year for the marine ornamental trade to graze on algae detrimental to aquarium species, however, little is known about popular species’ suitability to perform this clean-up crew role. Three commonly traded gastropods, Turbo bruneus, Tectus fenestratus, and Tegula eiseni were assessed on their performance. Their survival was quantified as was their movement, and positioning with respect to water level and growth rates were calculated from the start and end weights. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Thus, we ascribed this change in nitrite to dissolution from feces. Watson et al [52] reported that nitrite tolerance is species-specific, with species of the genus Turbo having higher tolerance to nitrite than other genera. They reported that mortality of two turbinid gastropods, Tectus fenestratus and Tegula eiseni, was observed at low concentrations, whereas no adverse effects were observed in Turbo bruneus at concentrations up to 5 mg L −1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we ascribed this change in nitrite to dissolution from feces. Watson et al [52] reported that nitrite tolerance is species-specific, with species of the genus Turbo having higher tolerance to nitrite than other genera. They reported that mortality of two turbinid gastropods, Tectus fenestratus and Tegula eiseni, was observed at low concentrations, whereas no adverse effects were observed in Turbo bruneus at concentrations up to 5 mg L −1 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the nitrite levels exceeded 5 mg L −1 on the fifth day at all temperatures, suggesting that food consumption may have been affected by excess nitrite. However, because nitrite tolerance varies among species [47,49,52], the concentration that impacts the food consumption rate of this species For T. sazae, the rate increased with increasing water temperature. The rate per individual was highest at 25 • C, followed by 20 • C, 15 • C, 10 • C, and 5 • C; it showed a similar trend per unit biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation